La organización de los rasgos fonológicos en la fonología actual - Prieto, Pilar (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1992)
Since the seminal work by Jakobson, who proposed a set of unorganized binary features that could contrast between phonemes, recent research in phonology has dealt with the task of characterizing the units of speech. During the last fifteen years, and within the autosegmental framework, the goals of the theory of distinctive features started by Jakobson has changed a great deal; apart from characterizing and contrasting linguistic sounds, the organization of the features has now the goal of expressing the behavior and dependencies between features that are most commonly found in phonological processes across languages. In this article I present four recent models of feature representation, concentrating on the linguistic data and the arguments given for the existence and location of features and nodes. In the second section I concentrate on issues such as the universality of representations and the double behavior of certain sounds such as labiodentals, uvulars, and laryngeals; I suggest that all these cases involve articulatory differences across languages, which motivate their ambiguous phonological pattern.